A contribution to the thermal insulation performance characterization of corn cob particleboards - Paiva, Anabela (2012)
An alternative expedite experimental set-up is proposed to evaluate the thermal insulation performance of corn cob particleboards. Testing in situ thermal insulation performance under real thermal and hygrometric conditions, using more realistic sample dimensions, testing simultaneously several samples and monitoring continuously for several days the thermal behavior of a product are some advantages of this proposed technique. Therefore, it has shown to be accurate and versatile. Through this experimental methodology, a parametric thermal insulation study of the corn cob particleboard in which the impact of its thickness on its thermal insulation performance was also possible to perform. © 2011 Elsevier B.V.